Ultraviolet solar radiation in the tropical central Andes (12.0°S) - Suárez Salas, Luis F. (2017)
Ultraviolet (UV) solar irradiance measurements performed in the central Andes, Huancayo, Peru (12.0°S, 75.3°W, 3313 m asl) at 1 min intervals between January 2003 and December 2006 were used to analyse daily, monthly, and annual cycles of UV solar irradiance. The measurements were performed using a GUV-511 multi-channel filter radiometer at four wavelengths: 305, 320, 340, and 380 nm. UV irradiance data under clear sky and all sky conditions were separated using a procedure based on calculation of normalized irradiance. In February, the highest hourly mean value at noon for the UV Index reached 18.8 for clear sky conditions and 15.5 for all sky conditions, with outlier peaks close to UVI = 28. In addition, the highest mean value for the daily erythemal dose was found also in February, reaching 7.5 kJ m−2 d−1 with a maximum outlier value close to 10.1 kJ m−2 d−1. Comparisons between the clear sky GUV measurements and TUV model estimations were evaluated with statistical quantities showing values of R2 close to 0.98. The total ozone column and trace gases were obtained from OMI. The aerosol parameters were obtained from MODIS. The enhancements due to clouds of spectral irradiance at 340 nm as compared to a cloudless sky reach maxima of 20%. These results indicate that tropical central Andes has among the highest incident ultraviolet solar radiation in the world.